Penerapan model pembelajaran concept sentence dalam meningkatkan keterampilan menulis karangan narasi pada siswa kelas v sekolah dasar - Amalya Pratiwi; Hartono Hartono; Karsono Karsono (Didaktika Dwija Indria, 2020)
Abstarct. The purpose of this research is improving the narrative writing skills by applying concept sentence model. The form of this research is a Classroom Action Research with three cycles. The subject is 5th students at primary education school in the 2019/2020 school year, with a total of 31 students. Data collection techniques in this research using interviews, observation, field notes, test, and documentation. Then, data analysis of content by using validity and triangulation.While, the analysis of the data by using descriptive percentage and qualitative analysis technique.. The first cycle gets an average of 45,1%,, and the second cycle gets an average of 90,3%, ended the third cycle gets an average of 87%. Based on the result of the study, it can be conclude that the narrative writing skills of SD N Tunggulsari I in the 2019/2020 school year can be improved through the concept sentence model. The application of the concept sentence model can be applied by a teacher in improving narrative essay writing skills in the class.Keywords: Concept Sentence, narrative writing skill, classroom action research, primary education school